If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 1)(x + -7) = 0 Reorder the terms: (1 + x)(x + -7) = 0 Reorder the terms: (1 + x)(-7 + x) = 0 Multiply (1 + x) * (-7 + x) (1(-7 + x) + x(-7 + x)) = 0 ((-7 * 1 + x * 1) + x(-7 + x)) = 0 ((-7 + 1x) + x(-7 + x)) = 0 (-7 + 1x + (-7 * x + x * x)) = 0 (-7 + 1x + (-7x + x2)) = 0 Combine like terms: 1x + -7x = -6x (-7 + -6x + x2) = 0 Solving -7 + -6x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -1x)(7 + -1x) = 0Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Solution
x = {-1, 7}
| 8r^2-12r=0 | | 0=-16x^2+3x+1.3 | | 3x^2+34x+80=0 | | 18=3(d-1) | | 3-4(x+2)=15 | | x^3+x^2-x-1.7=0 | | 3a-32=-2a+23 | | 7(-6y+9)+4y=-13 | | (x*x)+(x*x)=36 | | 137-4x=23x+23 | | 20.4-2c=5 | | 4x+y+1=-y-2x+3 | | (a-b)(a^2+2ab+b^2)= | | 12y^2+2y=0 | | (2c-d)(2c^2+2cd+d^2)= | | 7-7x=29-21x | | 3x+10+x+2=2x+20 | | -3x+7=28 | | 3x-45=6 | | 7(n+6)+8(n+4)= | | 8(x+3)+14(x+2)=74 | | 3(6z-1)-4(z+9)=4(z+1) | | 0.02-2.6=5.38 | | p=3a+5b | | 4x-12=x+6 | | 5b*6b= | | 3x*5x*2x= | | 6(2z-1)-2(z+3)=3(z+1) | | 20y-10=10 | | 3a*4a= | | b/14=5/10 | | X+(-4)+2x=14 |